Priming and task‐specific training for arm weakness post stroke: A randomized controlled trial - Erin C. King; Jacob M. Schauer; Shyam Prabhakaran; Alexandra Wax; Sebastian Urday; Sangeetha Madhavan; Daniel M. Corcos; Mary Ellen Stoykov (Annals of Clinical and Translational Neurology)
Abstract Objective The objective of this work was to evaluate if task‐specific training (TST) preceded by bilateral upper limb motor priming (BUMP) reduces upper limb impairment more than TST preceded by control priming ([CP], sham electrical stimulation) in people with chronic stroke. Methods In this single‐blind, randomized controlled trial, 76 adults with moderate to severe upper limb hemiparesis ≥6 months post‐stroke were stratified by baseline impairment and randomized to receive either BUMP or CP prior to receiving the same TST protocol. Participants completed 30 h of treatment in 15 days over 6 weeks. The primary outcome was change in Fugl‐Meyer upper extremity (FMUE) from baseline to 8‐week follow‐up. We also report clinically meaningful response rates defined as a change in FMUE score of 6 points or greater. Results In response to treatment, both groups improved to a significant extent at follow‐up, exceeding the FMUE minimum clinically important difference. Those in BUMP and CP saw a mean change of 5.68 (SE 0.76, p < 0.001) and 5.87 (SE 0.76, p < 0.001) respectively. There was no significant difference between treatment arms (mean difference of −0.20 (95% CI = [−2.37, 1.97], SE = 1.08, p = 0.86)). A response of ≥6 points was observed in 46% in BUMP and 50% in CP. Interpretation There was no beneficial effect of BUMP. The magnitude of change seen in both groups reflects the largest improvement achieved with just 22.5 h of TST in this population, matching or out‐performing more invasive, time‐intensive, and costly interventions proposed in recent years.